Fractional calculus with applications for nuclear reactors dynamics - Saha Ray, Santanu (CRC Press, Taylor & Francis Group, 2016)
[This book] focuses on the application of fractional calculus to describe the physical behavior of nuclear reactors. It applies fractional calculus to incorporate the mathematical methods used to analyze the diffusion theory model of neutron transport and explains the role of neutron transport in reactor theory.